Investigating the in vivo functions of non-coding RNAs in Drosophila melanogaster - Schwarz, J (2015)
The number of annotated non-protein coding genes has increased dramatically in recent years, but the functions of very few are well understood. In this thesis, I study the functions of two classes of non-coding RNA in Drosophila melanogaster. Firstly, through characterisation of six putative long non-coding RNA loci containing transposon insertions, I identified a long non-coding RNA, lnc703, suitable for in depth characterisation. Using a GAL4/UAS fluorescent reporter I found lnc703 to be expressed in the larval fat body and confirmed this using qRT-PCR. Transcriptome profiling identified ribosomal genes as upregulated in two independent lnc703 mutant strains. Additionally, I have identified decreased lifespan in some lnc703gal4 strains and it will be interesting to determine whether there is a relationship between increased ribosomal protein gene expression and reduced lifespan. I also used transcriptome profiling of the musculature and CNS of miR-8 null larvae to determine tissue specific targets of miR-8. Many indirect effects of miR-8 were detected but using MRE prediction algorithms a number of potentially direct targets of miR-8 were identified. One of these, ilp5, which is upregulated in the CNS, was identified as a non-cell autonomous effect of loss of miR-8 in the fat body. Together this work highlights the importance of using multiple, complementary techniques to study the function of non-coding RNAs in vivo.